Answer:
the value of x are -9, -4
Explanation:
For (x + 4)(x + 9) to equal 0, either (x + 4) or (x + 9) must equal . The values of x that would result in the given expression being equal to 0
![(x + 4)(x + 9) = 0](https://img.qammunity.org/2019/formulas/mathematics/college/vu8zb3qn0r4rgaftp8axvk3ocm8481j7vj.png)
To find value of x , we set each factor =0 and solve for x
![x+4 =0](https://img.qammunity.org/2019/formulas/mathematics/college/z206iox437l16c5mdc1z9amvzx4n2l7at1.png)
Subtract 4 from both sides
x=-4
![x+9 =0](https://img.qammunity.org/2019/formulas/mathematics/college/y4o4zoyfzh2wp7oee28wjpy6e3lxbdicsn.png)
Subtract 9 from both sides
x=-9
So the value of x are -9, -4